Magnetic control silicon-based adhesive as well as preparation method and application thereof
By introducing magnetic nanomaterials and other modified components into silicon-based adhesives, the problem of degradation in moisture-heat environments is solved, and efficient filling of building gaps and good weather resistance is achieved.
Patent Information
- Application Number
- CN202411674445.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
AI Technical Summary
The performance of existing silicon-based adhesives in humid and heat environments has deteriorated and cannot effectively fill building gaps.
Magnetic silicon-based adhesives are used, and their components include silane-modified polyurethane, magnetic nanomaterials, microcrystalline silicon, nanocalcium carbonate, etc., and their adhesion, water resistance and aging resistance are improved through reasonable compounding and preparation methods.
It achieves stable performance in humid and hot environments, can effectively fill building gaps, improve repair efficiency and durability, and has good environmental protection performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building repair materials, and specifically relates to a magnetron silicon-based adhesive and a preparation method and application thereof. Background Art
[0002] With the acceleration of urbanization, building repair has become a huge market demand. Whether it is a new building or an old building, it needs regular repair and maintenance. Due to various practical limitations, traditional repair materials are often difficult to meet the various requirements in the field of modern building repair. Therefore, the development of new, high-performance building repair adhesives has become an urgent need in the construction industry.
[0003] Silicon-based materials have been widely used in the construction field due to their unique physical and chemical properties. Silicon-based materials have excellent high temperature resistance, oxidation resistance, and good chemical stability. In addition, silicon-based materials also have excellent adhesion and plasticity, making them ideal raw materials for building repair adhesives. However, existing silicone-based adhesives have poor fluidity. During the process of injecting glue into the gaps of building boards, the adhesive is usually injected directly into the gaps. After the injection is completed, the injected glue is scraped flat with a scraper. There is a problem that the adhesive cannot completely penetrate into the gaps, resulting in the gaps not being fully filled. At the same time, the existing silicone-based adhesives have poor stability and their performance deteriorates in a hot and humid environment.
[0004] Therefore, it is of great significance to develop an adhesive with good moisture and heat stability and the ability to fully fill the gaps. Summary of the invention
[0005] In view of the above-mentioned shortcomings, the purpose of the present invention is to provide a magnetron silicon-based adhesive and a preparation method and application thereof, so as to solve the technical problem that the performance of existing silicon-based adhesives deteriorates in a hot and humid environment and cannot effectively fill building gaps.
[0006] To achieve the above object, the present invention is implemented through the following technical solutions: In a first aspect, the present invention provides a magnetron silicon-based adhesive, comprising, by weight: 60-70 parts of silane-modified polyurethane, 15-25 parts of silane coupling agent, 40-60 parts of magnetic nanomaterials, 15-45 parts of microcrystalline silicon, 25-40 parts of nano calcium carbonate, 5-15 parts of titanium dioxide, 5-10 parts of talc, 10-15 parts of aminosilane, 3-8 parts of color paste, and 1-4 parts of catalyst.
[0007] Preferably, the preparation method of silane-modified polyurethane comprises the following steps: S1. The silane-modified polyurethane prepolymer, the plasticizer, and the first coupling agent are uniformly mixed at 50-70° C. under vacuum conditions to obtain a first mixture; S2. The first mixture is mixed with hydrated silicate, titanium dioxide and calcium carbonate at 100-110° C. under vacuum conditions to obtain a second mixture; S3. The second mixture, the second coupling agent and dibutyltin dilaurate are mixed evenly under vacuum conditions to obtain a silane-modified polyurethane.
[0008] Preferably, the silane-modified polyurethane prepolymer is one or more of isocyanate ethyl trimethoxy silane, isocyanate ethyl triethoxy silane, isocyanate propyl trimethoxy silane, and isocyanate propyl triethoxy silane; the first coupling agent is one or more of silane coupling agents A-171 and A-151; and the second coupling agent is one or more of silane coupling agents A-1110 and A-1100.
[0009] Preferably, the silane coupling agent is one or more of vinyltriethoxysilane, β-methoxyethoxysilane, and KH-550.
[0010] Preferably, the particle size of the magnetic nanomaterial is 100-500 nm.
[0011] Preferably, the magnetic nanomaterial is nano nickel-iron alloy, nano iron-cobalt alloy, nano iron-nickel-cobalt alloy, nano Fe 2 O 3 、Nano-Fe 3 O 4 、Nano CoFe 2 O 4 、Nano MnFe 2 O 4 、Nano NiFe 2 O 4 One or more of .
[0012] Preferably, the particle size of nano calcium carbonate is 0.01-0.05 μm. As a structural and reinforcing filler, nano calcium carbonate can significantly improve the adhesion, tensile strength, modulus and hardness of the adhesive.
[0013] Preferably, the catalyst is one or more of tin butyrate and dibutyltin dioctoate.
[0014] In a second aspect, the present invention provides a method for preparing a magnetron silicon-based adhesive, comprising the following steps: uniformly mixing silane-modified polyurethane, a silane coupling agent, microcrystalline silicon, aminosilane, a catalyst, and nano-calcium carbonate to obtain a first material; uniformly mixing the first material with talcum powder, titanium dioxide, and a color paste to obtain a second material; and uniformly mixing the second material with a magnetic nanomaterial to obtain a magnetron silicon-based adhesive.
[0015] In a third aspect, the present invention provides a use of the magnetron silicon-based adhesive as described in the first aspect in building repair.
[0016] The beneficial effects of the present invention are: The magnetron silicon-based adhesive provided by the present invention has good bonding strength and excellent water resistance and aging resistance through the reasonable compounding of silane-modified polyurethane, magnetic nanomaterials and microcrystalline silicon. At the same time, the introduction of magnetic nanomaterials can not only cooperate with electromagnetic equipment to realize remote repair, but also make the adhesive completely fill into the building gap under the action of magnetic force, making the repair more effective, efficient and convenient. Moreover, during the curing process, it can occupy a certain space, which helps to reduce the thermal expansion coefficient of the adhesive, so that it can still maintain stable performance in a high temperature environment.
[0017] The magnetron silicon-based adhesive provided by the present invention has excellent bonding strength with various building materials. This bonding strength is not only strong but also long-lasting and can withstand various changes in environmental conditions. Microcrystalline silicon, magnetic nanomaterials and silane-modified polyurethane give it excellent weather resistance and aging resistance. Compared with traditional silicon-based adhesives, it has more stable properties, which enables it to maintain good performance under harsh weather conditions (such as high temperature, low temperature, rain and snow, etc.) and is not easy to age and fail.
[0018] The magnetron silicon-based adhesive provided by the present invention has good fluidity and plasticity, and is easy for construction workers to operate. At the same time, its curing time is moderate, and the repair work can be completed in a shorter time, thereby improving construction efficiency; the pollution generated during production and use is small, which meets environmental protection requirements, and after curing, it is non-toxic and harmless, and will not cause harm to the environment and human health. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The embodiment of the present invention provides a magnetron silicon-based adhesive, which includes, by weight: 60-70 parts of silane-modified polyurethane, 15-25 parts of silane coupling agent, 40-60 parts of magnetic nanomaterials, 15-45 parts of microcrystalline silicon, 25-40 parts of nano calcium carbonate, 5-15 parts of titanium dioxide, 5-10 parts of talcum powder, 10-15 parts of aminosilane, 3-8 parts of color paste, and 1-4 parts of catalyst. Among them, the silane coupling agent is one or more of vinyl triethoxysilane, β-methoxyethoxysilane, and KH-550; the particle size of the magnetic nanomaterial is 100-500nm, including but not limited to nano nickel-iron alloy, nano iron-cobalt alloy, nano iron-nickel-cobalt alloy, nano Fe 2 O3 、Nano-Fe 3 O 4 、Nano CoFe 2 O 4 、Nano MnFe 2 O 4 、Nano NiFe 2 O 4 One or more of the following: the particle size of nano calcium carbonate is 0.01-0.05 μm; the catalyst is one or more of tin butyrate and dibutyltin dioctoate.
[0021] In some preferred embodiments, the silane-modified polyurethane comprises, by weight, 60 parts of silane-modified polyurethane prepolymer, 15 parts of plasticizer, 5 parts of hydrated silicate, 4 parts of titanium dioxide, 30 parts of calcium carbonate, 10 parts of a first coupling agent, 5 parts of a second coupling agent, and 2 parts of dibutyltin dilaurate. The preparation method comprises the following steps: S1. Mixing a silane-modified polyurethane prepolymer, a plasticizer, and a first coupling agent at 50-70° C. under vacuum to obtain a first mixture; the silane-modified polyurethane prepolymer is one or more of isocyanate ethyl trimethoxy silane, isocyanate ethyl triethoxy silane, isocyanate propyl trimethoxy silane, and isocyanate propyl triethoxy silane; and the first coupling agent is one or more of silane coupling agents A-171 and A-151; S2. The first mixture is mixed with hydrated silicate, titanium dioxide and calcium carbonate at 100-110° C. under vacuum conditions to obtain a second mixture; S3. The second mixed material, the second coupling agent and dibutyltin dilaurate are mixed evenly under vacuum conditions to obtain silane-modified polyurethane. The second coupling agent is one or more of silane coupling agents A-1110 and A-1100.
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below.
[0023] The silane-modified polyurethane used in the following examples was prepared by the following method: S1. In parts by weight, weigh 60 parts of isocyanate ethyl triethoxysilane, 15 parts of dioctyl phthalate, 5 parts of hydrated silicate, 4 parts of titanium dioxide, 30 parts of calcium carbonate, 10 parts of the first coupling agent, 5 parts of the second coupling agent, and 2 parts of dibutyltin dilaurate.
[0024] S2. Stirring isocyanate ethyl triethoxysilane, dioctyl phthalate, and silane coupling agent A-171 at 70° C. under vacuum conditions for 1 hour to obtain a first mixture; S3. The first mixture is stirred with hydrated silicate, titanium dioxide and calcium carbonate at 100° C. under vacuum conditions for 2 h to obtain a second mixture; S4. After the second mixture is cooled to room temperature, it is mixed with silane coupling agent A-1110 and dibutyltin dilaurate and stirred for 40 minutes under vacuum conditions to obtain a silane-modified polyurethane.
[0025] Example 1 60 parts of silane-modified polyurethane, 15 parts of vinyl triethoxysilane, 20 parts of microcrystalline silicon, 10 parts of aminosilane, 3 parts of tin butyrate, and 30 parts of nano calcium carbonate were put into a reactor and stirred for 20 minutes to obtain a first material; 5 parts of talc, 5 parts of titanium dioxide, and 5 parts of color paste were sequentially added into the reactor and stirred for 30 minutes to obtain a second material; finally, 50 parts of ferroferric oxide nano magnetic powder were added and stirred for 30 minutes to obtain a magnetron silicon-based adhesive.
[0026] Example 2 70 parts of silane-modified polyurethane, 25 parts of β-methoxyethoxysilane, 45 parts of microcrystalline silicon, 15 parts of aminosilane, 4 parts of tin butyrate, and 40 parts of nano calcium carbonate were put into a reactor and stirred for 20 minutes to obtain a first material; 10 parts of talcum powder, 15 parts of titanium dioxide, and 8 parts of color paste were sequentially added into the reactor and stirred for 30 minutes to obtain a second material; finally, 60 parts of ferroferric oxide nano magnetic powder were added and stirred for 30 minutes to obtain a magnetron silicon-based adhesive.
[0027] Example 3 65 parts of silane-modified polyurethane, 15 parts of KH-550, 15 parts of microcrystalline silicon, 10 parts of aminosilane, 1 part of dibutyltin dioctoate, and 25 parts of nano-calcium carbonate were put into a reactor and stirred for 20 minutes to obtain a first material; 5 parts of talc, 10 parts of titanium dioxide, and 3 parts of color paste were sequentially added into the reactor and stirred for 30 minutes to obtain a second material; finally, 40 parts of ferroferric oxide nano-magnetic powder were added and stirred for 30 minutes to obtain a magnetron silicon-based adhesive.
[0028] Comparative Example 1 60 parts of silane-modified polyurethane, 15 parts of vinyl triethoxysilane, 20 parts of microcrystalline silicon, 10 parts of aminosilane, 3 parts of tin butyrate, and 30 parts of nano calcium carbonate were put into a reactor and stirred for 20 minutes to obtain the first material; 5 parts of talcum powder, 5 parts of titanium dioxide, and 5 parts of color paste were added to the reactor in sequence and stirred for 30 minutes to obtain a silicone-based adhesive.
[0029] Comparative Example 2 60 parts of silane-modified polyurethane, 15 parts of vinyl triethoxysilane, 10 parts of aminosilane, 3 parts of tin butyrate, and 30 parts of nano calcium carbonate were put into a reactor and stirred for 20 minutes to obtain a first material; 5 parts of talc, 5 parts of titanium dioxide, and 5 parts of color paste were sequentially added into the reactor and stirred for 30 minutes to obtain a second material; finally, 50 parts of ferroferric oxide nano magnetic powder were added and stirred for 30 minutes to obtain a magnetron silicon-based adhesive.
[0030] The performance tests were performed on the adhesives prepared in Example 1 and Comparative Examples 1 and 2. The results are shown in Table 1.
[0031] Table 1
[0032] As can be seen from Table 1, the magnetic silicon-based repair adhesive provided by the present invention exhibits excellent performance in terms of bonding strength, temperature resistance, etc., is suitable for various bonding repair scenarios, and has high market application value. Compared with Comparative Example 1, Example 1 has good bonding strength and moisture and heat stability, indicating the technical contribution made by magnetic nanomaterials; compared with Comparative Example 2, Example 1 also has excellent bonding strengths such as tensile strength and shear strength, and in high temperature, low temperature, humidity and other environmental simulation tests, the bonding strength fluctuation range is extremely small, indicating the technical contribution made by microcrystalline silicon.
[0033] In summary, the addition of magnetic nanomaterials makes the present invention more efficient and convenient in the repair process. At the same time, during the curing process, it can occupy a certain space, reduce the shrinkage of the adhesive, and also help to reduce the thermal expansion coefficient of the adhesive, so that it can still maintain stable performance in a high temperature environment. When nano calcium carbonate is used as a filler and reinforcing agent, it can greatly reduce the cost of the product and improve the processing performance of the product. Microcrystalline silicon can enhance the resistance of the adhesive to chemical substances such as acids and alkalis, and improve the corrosion resistance of the repaired surface. The present invention can select different color pastes according to different buildings, which ensures the quality of the repair while also ensuring the integrity and aesthetics of the building repair.
[0034] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.
[0035] The above-mentioned embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A magnetron silicon-based adhesive, characterized in that: Calculated by weight, it includes: 60-70 parts of silane modified polyurethane, 15-25 parts of silane coupling agent, 40-60 parts of magnetic nano material, 15-45 parts of microcrystalline silicon, 25-40 parts of nano calcium carbonate, 5-15 parts of titanium dioxide, 5-10 parts of talc, 10-15 parts of aminosilane, 3-8 parts of color paste and 1-4 parts of catalyst.
2. The magnetron silicon-based adhesive according to claim 1, characterized in that: The preparation method of the silane-modified polyurethane comprises the following steps: S1. The silane-modified polyurethane prepolymer, the plasticizer, and the first coupling agent are uniformly mixed at 50-70° C. under vacuum conditions to obtain a first mixture; S2. The first mixture is mixed with hydrated silicate, titanium dioxide and calcium carbonate at 100-110°C under vacuum to obtain a second mixture; S3. The second mixture, the second coupling agent and dibutyltin dilaurate are mixed uniformly under vacuum conditions to obtain a silane-modified polyurethane.
3. The magnetron silicon-based adhesive according to claim 2, characterized in that: The silane-modified polyurethane prepolymer is one or more of isocyanate ethyl trimethoxy silane, isocyanate ethyl triethoxy silane, isocyanate propyl trimethoxy silane, and isocyanate propyl triethoxy silane; the first coupling agent is one or more of silane coupling agents A-171 and A-151; the second coupling agent is one or more of silane coupling agents A-1110 and A-1100.
4. The magnetron silicon-based adhesive according to claim 1, characterized in that: The silane coupling agent is one or more of vinyl triethoxy silane, β-methoxyethoxy silane and KH-550.
5. The magnetron silicon-based adhesive according to claim 1, characterized in that: The particle size of the magnetic nanomaterial is 100-500nm.
6. The magnetron silicon-based adhesive according to claim 5, characterized in that: The magnetic nanomaterial is one or more of nano nickel-iron alloy, nano iron-cobalt alloy, nano iron-nickel-cobalt alloy, nano Fe2O3, nano Fe3O4, nano CoFe2O4, nano MnFe2O4, and nano NiFe2O4.
7. The magnetron silicon-based adhesive according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 0.01-0.05 μm.
8. The magnetron silicon-based adhesive according to claim 1, characterized in that: The catalyst is one or more of tin butyrate and dibutyltin dioctoate.
9. A method for preparing a magnetron silicon-based adhesive according to any one of claims 1 to 8, characterized in that: The following steps are involved: Evenly mixing silane-modified polyurethane, silane coupling agent, microcrystalline silicon, aminosilane, catalyst and nano-calcium carbonate to obtain a first material; The first material is mixed evenly with talcum powder, titanium dioxide and color paste to obtain a second material; The second material is mixed evenly with the magnetic nanomaterial to obtain the magnetron silicon-based adhesive.
10. Use of the magnetron silicon-based adhesive according to any one of claims 1 to 8 in building repair.
Citation Information
Cited By
Magnetic nail-free glue and preparation method thereof
CN121271483A
A magnetic adsorption nail-free adhesive and a preparation method thereof
CN121271483B